if x-iy =
![\sqrt{a-ib \div c - id} \sqrt{a-ib \div c - id}](https://tex.z-dn.net/?f=+%5Csqrt%7Ba-ib+%5Cdiv+c+-+id%7D+)
prove that
![{x}^{2} + {y}^{2} = \frac{ {a + {b}^{2} } }{ {c + {d}}^{2} } {x}^{2} + {y}^{2} = \frac{ {a + {b}^{2} } }{ {c + {d}}^{2} }](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2%7D++%2B++%7By%7D%5E%7B2%7D+++%3D++%5Cfrac%7B+%7Ba+%2B++%7Bb%7D%5E%7B2%7D+%7D+%7D%7B+%7Bc+%2B++%7Bd%7D%7D%5E%7B2%7D+%7D++)
Answers
Answered by
0
Answer:
just a few days later this morning someone called a friend and said he was going to call you and ask if he had a good time for him to call him and he said he was going to call him.
Similar questions